O sentido da ontologia do espaço para a dissolução da dicotomia geografia física-geografia humana : estudo sobre o caso da geografia crítica brasileira a partir do pensamento de Martin Heidegger - Calçavara, Reginaldo Alex (2013)
The study articulates the themes of ontology of space and the dichotomy between Physical Geography and Human Geography in the renewal movement critical of Brazilian geography. Seeks to demonstrate that there is a link between, on the one hand, the position taken by this part of Brazilian geography forward that dichotomy, and on the other hand, the ontological reflection about the object of discipline, directly influenced by Marxism. Indicates how alternative field of ontological thinking approach of the German philosopher Martin Heidegger on the question of being, especially within the scope and centrality of this issue in the work of that philosopher s perspective the question of technique, redefining the notion of production, would provide a horizon alternative ontology in geography capable, it is suggested, opening the question of being as a question to be thought,